Enhancing Decision-Making Capacity through Data Governance Framework Implementation - Vijayan, Deepthi (Journal of Global Economy, Business and Finance, 2025)
Robust data governance frameworks are becoming increasingly necessary for enterprises to make effective decisions. This study looks at how important data governance is in promoting better decision-making by guaranteeing the accuracy, security, and integrity of organizational data. It demonstrates how businesses may strategically create and implement data governance structures, policies, and procedures by referencing accepted data governance principles and examining pertinent case studies. In addition to protecting data assets, these frameworks give stakeholders access to dependable and consistent data that is necessary for making well-informed decisions. The research shows that organizational agility and competitiveness are greatly enhanced by well-designed data governance frameworks through a synthesis of theoretical ideas and real-world examples. Additionally, it highlights the importance of proactive data management at every stage of the data lifecycle, from collection and storage to analysis. It also highlights the need for proactive data management from collection and storage to analysis and distribution. In the end, the results emphasize how data governance may significantly improve an organization's capacity for making decisions, and they support the methodical implementation of data governance as a fundamental component of contemporary business strategy.